2016
DOI: 10.1176/appi.neuropsych.15050106
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation of Cerebral Blood Flow and Amyloid Burden in Veterans With and Without Combat-Related Traumatic Brain Injury

Abstract: This study aimed to examine global and regional cerebral blood flow and amyloid burden in combat veterans with and without traumatic brain injury (TBI). Cerebral blood flow (in milliliters per minute per 100 mL) was measured by quantitative [(15)O]water, and amyloid burden was measured by [(11)C]PIB imaging. Mean global cerebral blood flow was significantly lower in veterans with TBI compared with non-TBI veterans. There were essentially no differences between groups for globally normalized regional cerebral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…19,[21][22][23] Briefly, all imaging was performed on an ECAT EXACT HR+Scanner (Siemens Medical Solutions USA, Inc, Knoxville, TN). Dynamic imaging (5 s/frame×20 frames) and arterial blood sampling commenced at tracer injection (45-50 mCi per injection) and continued for 100 seconds.…”
Section: Pet Imagingmentioning
confidence: 99%
“…19,[21][22][23] Briefly, all imaging was performed on an ECAT EXACT HR+Scanner (Siemens Medical Solutions USA, Inc, Knoxville, TN). Dynamic imaging (5 s/frame×20 frames) and arterial blood sampling commenced at tracer injection (45-50 mCi per injection) and continued for 100 seconds.…”
Section: Pet Imagingmentioning
confidence: 99%
“…Nevertheless, advanced MRI techniques (e.g., diffusion tensor imaging [DTI], arterial spin labeling [ASL]) have been utilized for in-vivo quantification of neurotrauma-related brain changes in Veterans (see Wilde et al, 2015 for review). However, while some studies find robust brain differences in Veterans with history of TBI relative to those with no history of head trauma ( Mac Donald et al, 2011 , Miller et al, 2016 , Petrie et al, 2014 , Ponto et al, 2016 ), others fail to detect any alterations ( Jorge et al, 2012 , Levin et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced CBF has been demonstrated to not only precede, but also directly contribute to negative WM micro- and macro-structural changes in older adults ( Bernbaum et al, 2015 , Brickman et al, 2009 , Promjunyakul et al, 2015 , Promjunyakul et al, 2016 , ten Dam et al, 2007 ). Importantly, while both CBF and WM changes have been independently examined within TBI ( Delano-Wood et al, 2015 , Ponto et al, 2016 , Vas et al, 2016 ), few studies have explored relationships between CBF and WM within this population. This is especially critical given CBF reductions could serve to exacerbate or contribute to any trauma-induced WM alterations well beyond the time of initial injury.…”
Section: Introductionmentioning
confidence: 99%
“…This notion, that mTBI is associated with a disrupted cerebrovascular system, also extends to blast-related mTBI. Recent work by Ponto et al 44 showed reduced global cerebral blood flow in blast-related mild and moderate TBI patients who were on average 3 years removed from their injury compared to veteran controls. In addition, residual cerebrovascular impairments have also been reported in pediatric mTBI, with reduced cerebral blood flow in bilateral frontotemporal regions 45 and bilateral thalami 46 in children who were 3-12 months removed from their injury compared to controls.…”
Section: Neuroimaging Evidence Of Cerebrovascular Dysfunction In Mtbimentioning
confidence: 99%